EVALUATION OF A GAMIFIED LEARNING EXPERIENCE: ANALYSIS OF FACTORS THAT IMPACT THE EFFECTIVENESS OF A GAMIFIED EXPERIENCE - Nair, Sridevi; Mathew, Jain (Revista Conhecimento Online: Diversidade e Inclusão Social, 2021)
Gamification has gone through a faddish cycle. It first gained prominence around 2012 and was quickly abandoned, as practitioners did not achieve the outcomes they expected. According to Gartner’s Hype Cycle, Gamification is at a point at which one might expect wide scale adoption. However, if history is not to repeat itself and results are to be achieved as theoretically predicted, a deeper understanding of the concept is essential. In the current study, the researchers attempt to evaluate a gamified learning experience. The participants were students of a Master in Business Administration course. The students were asked to participate in a gamified module and relevant data was collected, before and after the intervention. Based on a review of literature, the researchers identified the exogenous variables of Valence, Attitude towards use of Technology and Experience with Technology. The endogenous variables identified included Reaction and Learning. The findings of the study suggest that the gamified module resulted in increase in knowledge and that Attitude, Experience and Valence significantly predicted the Learner’s reaction to the experience. The findings of the study provide support to key theories in the area of gamification and insights for practitioners, on the factors to be considered before using a gamified learning intervention.